IMPLEMENTATION OF SUPERVISION IN IMPROVING THE LEARNING PROCESS AND CHARACTER EDUCATION IN ELEMENTARY SCHOOLS - Yudhie Suchyadi; Tatang Muhajang; Rini Sri Indriani; Mira Mirawati (Universitas Pakuan, 2022)
Supervision in schools is carried out by the principal who acts as a supervisor, so he must be able to carry out various supervision and control to improve teacher performance. Supervision and control are preventive measures to prevent teachers from making deviations and to be more careful in carrying out their work as educators. Therefore, this study revealed the supervision activities carried out by the Principal of SDN 14 Sungai Sirah, Sutera Subdistrict, Pesisir Selatan District. The results of this study are: 1). The focus of supervision activities carried out by the principal can be identified in two ways, namely; supervision activities involving the administration of teachers and teaching and learning activities, 2). Supervision activities are very helpful for teachers in solving educational problems faced by teachers when doing learning, and can provide motivation for teachers to always improve their knowledge to become professional teachers in carrying out learning, 3). Barriers to school principals in supervision are overlapping activities and limited operational funds.